ANALISA PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOUR, ORGANIZATIONAL JUSTICE DAN TRANSFORMATIONAL LEADERSHIP TERHADAP TURNOVER INTENTION DENGAN ORGANIZATIONAL COMMITMENT SEBAGAI MEDIASI PADA HOTELBINTANG 4 DI KOTA BATAM - S, Antony (REKAMAN (Jurnal Riset Ekonomi Bidang Akuntansi dan Manajemen), 2018)
Indonesia is currently a developing country, therefore employees, workers or HR become valuable assets for the company and the country. When an employee thinks to stop or leave the company, this will certainly cause losses to the company both in the long and short term. Therefore, companies must understand the variables that can reduce the employees turnover intention.This study uses a minimum sample of 335 hotel employees based on the Krejcie and Morgan tables, obtained through 355 questionnaires distributed at 4 stars hotels in Lubuk Baja region, namely; BCC Hotel & Residence, Crown Vista Batam Hotel, Grand I Hotel, Harmoni Suites Hotel, and Horizon Ultima Hotel. The sample selection using purposive sampling method. Data processing in this research using Statistical Package for Social Sciences (SPSS) and Partial Least Square (PLS) program. The final result showed that organizational citizenship behavior, organizational justice, and transformational leadership had a significant positive effect on turnover intention, with organizational commitment acting as mediation. So it can be concluded that organizational citizenship behavior, organizational justice, transformational leadership, organizational commitment can affect the turnover intention of employees of 4 star hotel in Batam City.